Retinal and thalamic alterations in the 5xFAD mouse model of Alzheimer’s disease - Shaylah McCool; Jennie C. Smith; Asia Sladek; Shan Fan; Matthew J. Van Hook (PLoS ONE, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by the formation of amyloid beta (Aβ) plaques and neurofibrillary tangles that lead to decreased quality of life due to behavioral, motor, and cognitive impairments. Due to the widespread pathological nature of AD, many brain regions are affected by Aβ plaques including regions important for vision such as the lateral geniculate nucleus (LGN) of the thalamus which is critical for relaying signals from the retina to the primary visual cortex. Using a wide range of techniques including electrophysiological approaches, in vivo and ex vivo imaging methods, and immunohistochemistry in a mouse model with progressing amyloidosis (5xFAD), the goal of this study was to determine whether AD-like pathology disrupts neuronal and synaptic structure and function in the visual system. In vivo electroretinogram recordings revealed photoreceptor dysfunction in the 6- and 9-month-old 5xFAD mice, while optical coherence tomography indicated no changes in 5xFAD retinal thickness from 9 to 12 months. In the dorsolateral geniculate nucleus (dLGN), the rodent homolog of the primate LGN, we identified decreased densities of retinal ganglion cell axon terminals and fewer thalamocortical (TC) neuron cell bodies. No detectable deficits in excitatory synaptic function or TC neuron dendritic structure were seen in the dLGN, and reflexive visual behavior was also found to be normal in the 5xFAD mice. These results indicate relatively modest amyloid-triggered dysfunction in these stages of the visual system suggesting that Aβ plaque formation may play only a small role in the visual system dysfunction seen in AD patients. These results may also point to potential compensatory mechanisms that preserve function of visual pathways in the 5xFAD visual system.